2020
DOI: 10.3389/fneur.2020.580572
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation in Cryptogenic Stroke Patients With Major-Vessel Occlusion

Abstract: Background and Purpose: To determine whether acute major-vessel occlusion (MVO) predicts atrial fibrillation (AF) in cryptogenic stroke (CS) patients, we analyzed the association between acute MVO and AF detected by insertable cardiac monitoring (ICM). Methods: We conducted a retrospective, multicenter, observational study of patients with CS who underwent ICM implantation between October 2016 and March 2018. In this analysis, we included follow-up data until June 2018. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Importantly, AF was diagnosed in 64.3% of patients with whole-territorial infarction patterns in initial neuroimaging. The presence of major-vessel occlusion is also a useful predictor of occult AF in the previous report ( 14 , 15 ). We analyzed more expanded concepts, such as the patients with major territorial infarctions without significant major vessel occlusion or apparently transient ischemic symptoms such as global aphasia with right-side weakness.…”
Section: Discussionmentioning
confidence: 67%
“…Importantly, AF was diagnosed in 64.3% of patients with whole-territorial infarction patterns in initial neuroimaging. The presence of major-vessel occlusion is also a useful predictor of occult AF in the previous report ( 14 , 15 ). We analyzed more expanded concepts, such as the patients with major territorial infarctions without significant major vessel occlusion or apparently transient ischemic symptoms such as global aphasia with right-side weakness.…”
Section: Discussionmentioning
confidence: 67%
“…A retrospective study from Japan demonstrated that the AF detection rate was 26.2% during a median follow-up of 221.5 days [13]. Furthermore, recent retrospective observational ICM studies have demonstrated that major-vessel occlusion (n=84) and frequent premature atrial contractions (n=66) were associated with AF detection after adjustment for risk factors and commodities, respectively [11,12]. Based on the results of these previous studies, we decided to enroll 200 patients in this observational study in order to perform statistical analyses, including multivariate regression analysis, with su cient statistical power.…”
Section: Sample Sizementioning
confidence: 99%
“…Further research on empiric anticoagulation is ongoing [ 14 ]. Recent investigations have strengthened the connection between AF and LVO [ 15 , 16 ]. In trials utilizing implantable and external cardiac monitors after cryptogenic stroke, the presence of LVO was the only independent predictor of AF besides age [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have strengthened the connection between AF and LVO [ 15 , 16 ]. In trials utilizing implantable and external cardiac monitors after cryptogenic stroke, the presence of LVO was the only independent predictor of AF besides age [ 15 , 16 ]. These findings highlight the LVO subgroup of AIS and the need for detailed occult AF investigation.…”
Section: Introductionmentioning
confidence: 99%